Biological control of Meloidogyne incognita race 2 on soybean (Glycine max (L.) Merrill) by means of plant growth-promoting rhizobacteria - Labuschagne, Nico (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2018.